Communication-less harmonic compensation in a multi-bus microgrid through autonomous control of distributed generation grid-interfacing converters - Ding, Guangqian (2018)
This paper proposes a novel approach to compensate buses voltage and current harmonics through distributed generation (DG) interfacing converter in a multi-bus microgrid. The control approach of each individual DG unit was designed to use only feedback variables of the converter itself that can be measured locally. In the proposed approach, the adjacent bus voltage is indirectly derived from the measured DG converter output voltage, DG line current and line impedance. A voltage closed-loop controller and a current closed-loop controller are designed to achieve both functions of DG real power generation and harmonics compensation. Therefore, the traditional harmonic measurement devices installed at the bus as well as the long distance communication between the bus and the DG converter are not required. The proposed approach can compensate the current harmonics, mitigate the buses voltage distortion and enable the customer devices to be operated in normal conditions within the multi-bus microgrid, and meanwhile relieve the burden of power quality regulator installed at the point of common coupling. Matlab simulations and experimental results are presented to show the operational effectiveness of the proposed approach.